As políticas para a educação física escolar e esporte durante o regime militar - Pereira, Andressa Braw Brito [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The period of the military rule in Brazil occurred between 1964 and 1985, when the Armed Forces exercised total control over the state apparatus and the educational and cultural fields, like any other, were exploited in such a way that their needs - as an authoritarian regime - were backed. This study’s objective was to recollect this historic moment and analyze its public policies for school physical education and sport. Towards this end, documentary and bibliographic research was done using legislation, books and scientific articles on the subject of study. After using the Content Analysis technique, the categories “Strengthening Physical Education?”; “Sportivization of Physical Education” and “Biologization of Physical Education” emerged

O período do regime militar ocorreu entre 1964 e 1985 e nele as Forças Armadas exerceram total controle sobre o aparelho do Estado, os campos educacional e cultural, como qualquer outro, foi utilizado de modo que suas necessidades - enquanto regime autoritário - obtivessem respaldo. O objetivo deste trabalho foi o de resgatar esse momento histórico e analisar as suas políticas públicas para a educação física escolar e o esporte. Para tanto, foram realizadas pesquisas documental e bibliográfica, utilizando-se de legislações, livros e artigos científicos sobre o tema de estudo. Após o emprego da técnica de Análise do Conteúdo sobre as políticas públicas, as categorias Fortalecimento da Educação Física?; Esportivização da Educação Física e Biologização da Educação Física emergiram.
The policies for school physical education and sport during the military regime
Keywords: History of physical education; Educational policies; Military regime in Brazil; História da Educação física; Políticas educacionais; Regime militar no Brasil